1997
DOI: 10.1007/bf02936967
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage into a simple liver cyst: Diagnostic implications of a recent case

Abstract: Hemorrhage complicating simple liver cyst is rare. On imaging studies, the differential diagnosis between intracystic hemorrhage and cystadenocarcinoma of the liver is unreliable, and hepatectomy has been performed for benign liver cyst in this situation. We describe the characteristics of hemorrhage into a liver cyst in a patient who underwent dome resection of the cyst. In our patient, important diagnostic findings included benign cytologic features in a cyst fluid specimen aspirated with ultrasonographic gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 6 publications
2
24
1
1
Order By: Relevance
“…Therefore, this discordance between US and CT findings is important for establishing the diagnosis of simple liver cysts associated with intracystic hemorrhage. [5][6][7][8] In recent years, MRI has frequently been used for diagnosing liver disease. In 1993, Vilgrain et al 9 evaluated MRI findings of intracystic hemorrhage in simple liver cysts, and reported that high signals from clot formation detected by T1-weighted sequence were very useful for differentiating blood clot in the cysts from cystic liver tumor exhibiting low signals.…”
Section: Figmentioning
confidence: 99%
“…Therefore, this discordance between US and CT findings is important for establishing the diagnosis of simple liver cysts associated with intracystic hemorrhage. [5][6][7][8] In recent years, MRI has frequently been used for diagnosing liver disease. In 1993, Vilgrain et al 9 evaluated MRI findings of intracystic hemorrhage in simple liver cysts, and reported that high signals from clot formation detected by T1-weighted sequence were very useful for differentiating blood clot in the cysts from cystic liver tumor exhibiting low signals.…”
Section: Figmentioning
confidence: 99%
“…They are common and benign, usually asymptomatic, and require no treatment [15,25]. They occasionally resolve spontaneously, but can also cause serious complications [4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23]26]. Fong et al reviewed the literature on hemorrhagic hepatic cysts [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cytologic examination of cystic fluid obtained by aspiration may provide important information for distinguishing malignant from benign lesions [11]. However, aspiration of a cystic lesion can lead to tumor spread.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations